Determination of the total antioxidant and oxidant status of some galactagogue and herbal teas - D. Ağagündüz (Food Science and Human Wellness)
This research was aimed to evaluate the total antioxidant status (TAS) and the total oxidant status (TOS) of galactagogues and herbal teas. Galactagogues and herbal teas used for other purposes were sold in the market for breastfeeding mothers and babies. Tea infusions were prepared by following brewing recipe on the package. TAS (mmol/L) and TOS (μmol/L) were measured and oxidative stress indices (OSI) were calculated. TAS values of the mixed-herbal teas in granule form that sold as still tea were found to be higher ((1.5 ± 0.00)–(1.7 ± 0.14) mmol/L) compared to other galactagogue tea types (P < 0.05). TAS value of the mixed-herbal tea in classic tea bag was (1.0 ± 0.06) mmol/L while the TAS value of the vitamin added mixed-herbal tea was (3.0 ± 0.00) mmol/L (P <  0.05). The TAS and TOS values of the night-teas were simultaneously found to be higher compared to herbal teas (P < 0.05). Besides, the highest OSI values among herbal teas was chamomile tea (6.96). In conclusion, antioxidant/oxidant status of galactagogues and other herbal teas might vary according to their form (powder or granule), type, variety of herbs in the composition, and the brand. Moreover, some galactagogues and other herbal teas have high levels of oxidant activity as well as antioxidant activity. Also, it seems that vitamin addition is important for balancing antioxidant/oxidant status of all tea types.